Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
\(x=\left(1-\frac{1}{2}\right).\left(1-\frac{1}{4}\right)\left(1-\frac{1}{6}\right)\left(1-\frac{1}{8}\right)\left(1-\frac{1}{10}\right)\)
\(=\frac{1}{2}.\frac{3}{4}.\frac{5}{6}.\frac{7}{8}.\frac{9}{10}=\frac{63}{256}< \frac{63}{210}=0,3\)
\(x=\sqrt{0,1}>\sqrt{0,09}=0,3\)
=> y<x
![](https://rs.olm.vn/images/avt/0.png?1311)
ta có \(\left(\frac{1}{25}\right)^{\frac{1}{3}log^{10}_5}=\left(\frac{1}{5}\right)^{\frac{2}{3}log^{10}_5}=\left(\left(\frac{1}{5}\right)^{log^{10}_5}\right)^{\frac{2}{3}}=\left(5^{log^{10}_5}\right)^{-\frac{2}{3}}=10^{-\frac{2}{3}}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
a: \(=\dfrac{37}{25}\cdot\dfrac{25}{74}\cdot\dfrac{4}{5}=\dfrac{1}{2}\cdot\dfrac{4}{5}=\dfrac{2}{5}\)
b: \(=\dfrac{6}{11}\cdot\dfrac{11}{5}:\dfrac{16}{9}=\dfrac{6}{5}\cdot\dfrac{9}{16}=\dfrac{54}{80}=\dfrac{27}{40}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
câu b:(3/10/99+4/10/99-5/8/299)*(1/2-1/3-1/6)
=(3/10/99+4/10/99-5/8/299)*(3/6-2/6-1/6)
=(3/10/99+4/10/99-5/8/299)*0
=0
(xEN*/7<=x+6<=43,x-1 chia hết cho 6)(tui nghĩ là vậy )
ta có \(\left(\frac{4}{5}\right)^{4log_{\frac{16}{25}}^3}=\left(\frac{16}{25}\right)^{2log_{\frac{16}{25}}^3}=\left(\left(\frac{16}{25}\right)^{log_{\frac{16}{25}}^3}\right)^2=3^2=9\)